2016
DOI: 10.1002/advs.201600243
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Area Carbon Nanosheets Doped with Phosphorus: A High‐Performance Anode Material for Sodium‐Ion Batteries

Abstract: Large‐area phosphorus‐doped carbon nanosheets (P‐CNSs) are first obtained from carbon dots (CDs) through self‐assembly driving from thermal treatment with Na catalysis. This is the first time to realize the conversion from 0D CDs to 2D nanosheets doped with phosphorus. The sodium storage behavior of phosphorus‐doped carbon material is also investigated for the first time. As anode material for sodium‐ion batteries (SIBs), P‐CNSs exhibit superb performances for electrochemical storage of sodium. When cycled at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
245
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 486 publications
(258 citation statements)
references
References 49 publications
11
245
0
2
Order By: Relevance
“…That demonstrates that an increased interlayer distance has a positive effect on the capacity at current densities above 2 A g −1 . Indeed, it has been shown that the enlarged distance between the graphene layers shortens the diffusion length for metal ions . A discharge‐charge cycling of the sample HG600a at high current densities resulted in an increase of the capacity when the measurements were repeated at 2 A g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…That demonstrates that an increased interlayer distance has a positive effect on the capacity at current densities above 2 A g −1 . Indeed, it has been shown that the enlarged distance between the graphene layers shortens the diffusion length for metal ions . A discharge‐charge cycling of the sample HG600a at high current densities resulted in an increase of the capacity when the measurements were repeated at 2 A g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the scarcity and uneven distribution of lithium resources limit the wide application of LIBs in large‐scale energy storage market . Sodium, which is chemically similar in many properties and abundantly distributed in the crust, is an alternative for lithium . Therefore, the energy storage system of sodium‐ion batteries (SIBs) has obvious advantages in resources and cost, and has great potential in the future.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations motivated the researchers to explore alternative carbon materials that are highly abundant of low cost and efficient without creating any environmental pollution. To date, biomass activated carbon, due to the developed pores, large specific surface area, abundant raw materials, good electrical conductivity, and mechanical properties, is widely used as electrode materials in electrochemical energy devices, which is derived from natural animals and plants, such as egg shell, cotton, peanut coat, seaweed, rice, Aspergillus oryzae , and so on …”
Section: Introductionmentioning
confidence: 99%